Diverse anthropogenic disturbances shift Amazon forests along a structural spectrum - Smith, Marielle N.; Stark, Scott C.; Taylor, Tyeen C.; Schietti, Juliana; Almeida, Danilo Roberti Alves de; Aragón, Susan; Torralvo, Kelly; Lima, Albertina P.; Oliveira, Gabriel de; Assis, Rafael Leandro de; Leitold, Veronika; Pontes-Lopes, Aline; et al. (Frontiers in Ecology and the Environment, 2023)
Amazon forests are being degraded by myriad anthropogenic disturbances, altering ecosystem and climate function. We analyzed the effects of a range of land-use and climate-change disturbances on fine-scale canopy structure using a large database of profiling canopy lidar collected from disturbed and mature Amazon forest plots. At most of the disturbed sites, surveys were conducted 10–30 years after disturbance, with many exhibiting signs of recovery. Structural impacts differed in magnitude more than in character among disturbance types, producing a gradient of impacts. Structural changes were highly coordinated in a manner consistent across disturbance types, indicating commonalities in regeneration pathways. At the most severely affected site – burned igapó (seasonally flooded forest) – no signs of canopy regeneration were observed, indicating a sustained alteration of microclimates and consequently greater vulnerability to transitioning to a more open-canopy, savanna-like state. Notably, disturbances rarely shifted forests beyond the natural background of structural variation within mature plots, highlighting the similarities between anthropogenic and natural disturbance regimes, and indicating a degree of resilience among Amazon forests. Studying diverse disturbance types within an integrated analytical framework builds capacity to predict the risk of degradation-driven forest transitions.
Keywords: climate change; anthropogenic effect; disturbance; forest canopy; forest ecosystem; human activity